Evolution of a lumileds – from "cool light" Loseva to lighting of streets (part II) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
In review are considered history development of semiconductor lumileds, done analysis up-to-date market lumileds, a new material and technology, are showed world tendencies and perspectives.